Inaccurate Assessments of Anterior Cranial Base Malignancy Following Nasoseptal Flap Reconstruction - Walsh, Erika; Illing, Elisa; Riley, Kristen O.; Cure, Joel; Srubiski, Aviva; Harvey, Richard J.; Woodworth, Bradford A. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objective The nasoseptal flap (NSF) provides vascularized tissue for repair of skull base defects of various etiologies. However, the NSF repair after skull base resection for anterior cranial base malignancies may demonstrate radiologic findings confusing for recurrent or residual disease on postoperative surveillance imaging. The objective of the current study was to review neuroradiologic misinterpretations of NSF reconstruction following anterior cranial base malignancies.Methods A multicenter review of patients reconstructed with the NSF after endoscopic resection of anterior cranial base malignancies from 2008 to 2013 was performed. Data were collected regarding etiology, surgical technique, locoregional control, and postoperative radiologic assessments. Only patients with at least one postoperative surveillance scan with inaccurate assessment of residual or recurrent malignancy were included in the study.Results Over 5 years, 13 patients were identified who had erroneous reporting of malignancy due to NSF reconstruction. On average, two neuroradiologists interpreted the NSF as persistent or recurrent malignancy over this time period (range: 1–7). The key findings suspicious for recurrence were enhancement and soft tissue thickening of the NSF. These findings were present in at least one postoperative scan in all patients.Conclusion Neuroradiologists and rhinologists performing surveillance on patients with a history of skull base malignancy with NSF reconstruction should maintain collaborative efforts to accurately interpret radiologic findings of the NSF during postoperative imaging.
Keywords: nasoseptal flap; endoscopic skull base surgery; cranial base; skull base tumor; endoscopic resection; endonasal skull base resection; skull base malignancy